2021
DOI: 10.4102/aosis.2020.bk210.10
|View full text |Cite
|
Sign up to set email alerts
|

Blending and cooperating in the computer literacy classroom: An opportunity to develop self-directed learning skills

Abstract: Peer review declarationThe publisher (AOSIS) endorses the South African 'National Scholarly Book Publishers Forum Best Practice for Peer Review of Scholarly Books'. The manuscript was subjected to a rigorous twostep peer review process prior to publication, with the identities of the reviewers not revealed to the author(s). The reviewers were independent of the publisher and/or authors in question. The reviewers commented positively on the scholarly merits of the manuscript and recommended that the manuscript … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 84 publications
(77 reference statements)
1
1
0
Order By: Relevance
“…Furthermore, the student teachers had opportunities to reflect on what was learnt and used formative assessments whilst providing constructive feedback regarding the learning progress (De Beer & Gravett, 2016). These results also concurred with the study of (Makonye, 2016) (Jordaan & Havenga, 2020;Kruger, 2020) and (Bailey & Lubbe, 2020) where all concluded that the promotion of SDL in HEIs will enable the student teachers to solve mathematics problems actively and effectively.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, the student teachers had opportunities to reflect on what was learnt and used formative assessments whilst providing constructive feedback regarding the learning progress (De Beer & Gravett, 2016). These results also concurred with the study of (Makonye, 2016) (Jordaan & Havenga, 2020;Kruger, 2020) and (Bailey & Lubbe, 2020) where all concluded that the promotion of SDL in HEIs will enable the student teachers to solve mathematics problems actively and effectively.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, (Jordaan & Havenga, 2020) report in the study "University-school initiative for a career in engineering: development of self-directed learning when solving mathematics problems", that learners develop self-directed learning skills when introduced to solving mathematics problems. In addition, the investigation of blending and cooperating in the computer literacy classroom: an opportunity to develop self-directed learning skills by (Bailey & Lubbe, 2020) reveals that educator enhances and equips pre-service teachers' SDL abilities in computer literacy by allowing them to assume responsibility with or without the assistance of other pre-service teachers.…”
Section: Self-directed Learningmentioning
confidence: 99%